Analysis of the quality of work life of small and medium-sized companies in Southern Sonora, through artificial neuronal networks (Revista de Investigaciones Universidad del Quindío, 2021)
In this research, an artificial neural network analysis was carried out for 356 small and medium-sized companies in the South of Sonora, SMEs represent 99.8% of the economic units of the country with more than 4.1 million companies, according to official data from Inegi this type of companies that contribute 42% of the Gross Domestic Product (GDP) and generate 78% of employment.To determine their quality of working life, an instrument was used where companies were evaluated in four dimensions: individual well-being, working conditions and environment, organization and well-being achieved through work. The results obtained showed a quality of work life of 85.25%, with this applied methodology it demonstrates the relevance of the study applicable at the national and international level.
Keywords: Quality of work life; workers; artificial neural network; companies